Prediction of cardiac events with non‐contrast magnetic resonance feature tracking in patients with ischaemic cardiomyopathy. (24th November 2021) - Overhoff, Daniel; Ansari, Uzair; Hohneck, Anna; Tülümen, Erol; Rudic, Boris; Kuschyk, Jürgen; Lossnitzer, Dirk; Baumann, Stefan; Froelich, Matthias F.; Waldeck, Stephan; Akin, Ibrahim; Borggrefe, Martin; et al.
Abstract: Aims: The aim of this study was to evaluate the prognostic value of feature tracking (FT) derived cardiac magnetic resonance (CMR) strain parameters of the left ventricle (LV)/right ventricle (RV) in ischaemic cardiomyopathy (ICM) patients treated with an implantable cardioverter‐defibrillator (ICD). Current guidelines suggest a LV‐ejection fraction ≤35% as major criterion for ICD implantation in ICM, but this is a poor predictor for arrhythmic events. Supplementary parameters are missing. Methods and results: Ischaemic cardiomyopathy patients ( n  = 242), who underwent CMR imaging prior to primary and secondary implantation of ICD, were classified depending on EF ≤ 35% ( n  = 188) or >35% ( n  = 54). FT parameters were derived from steady‐state free precession cine views using dedicated software. The primary endpoint was a composite of cardiovascular mortality (CVM) and/or appropriate ICD therapy. There were no significant differences in FT‐function or LV‐/RV‐function parameters in patients with an EF ≤ 35% correlating to the primary endpoint. In patients with EF > 35%, standard CMR functional parameters, such as LV‐EF, did not reveal significant differences. However, significant differences in most FT parameters correlating to the primary endpoint were observed in this subgroup. LV‐GLS (left ventricular‐global longitudinal strain) and RV‐GRS (right ventricular‐global radial strain) revealed the best diagnostic performance in ROC curve analysis. The combination of LV‐GLS and RV‐GRS showed a sensitivity of 85% and a specificity of 76% for the prediction of future events. Conclusions: The impact of FT derived measurements in the risk stratification of patients with ICM depends on LV function. The combination of LV‐GLS/RV‐GRS seems to be a predictor of cardiovascular mortality and/or appropriate ICD therapy in patients with EF > 35%.